2023
DOI: 10.1111/ffe.14219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of confining pressure strength on the characteristics of energy evolution and fatigue fracture of the coal‐rock structural body

Tan Li,
Zihan Yue,
Jingkai Li
et al.

Abstract: The stability of coal seam‐overlying strata is significant to the safety of coal mines. The coal‐rock height ratio and confining pressure strength affect the stability of coal seam‐overlying strata. The research purpose of this paper is to obtain the effects of confining pressure and coal‐rock height ratio on the mechanical properties, energy evolution characteristics, and damage variables of structural body through the uniaxial loading, uniaxial cyclic loading, and triaxial cyclic loading experiment. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Their findings indicated that higher confining pressures resulted in the accumulation of more elastic strain energy in the coal prior to failure. Li et al [11] proposed the concept of an energy dissipation ratio to examine the influence of confining pressure on the mechanical properties and damage evolution of rock structures using triaxial cyclic load experiments. Du et al discovered that the ultimate strength and residual strength of coal samples exhibited a linear increase with confining pressure, and that confining pressure could impede crack expansion while enhancing the energy storage capacity of coal [12].…”
Section: Introductionmentioning
confidence: 99%
“…Their findings indicated that higher confining pressures resulted in the accumulation of more elastic strain energy in the coal prior to failure. Li et al [11] proposed the concept of an energy dissipation ratio to examine the influence of confining pressure on the mechanical properties and damage evolution of rock structures using triaxial cyclic load experiments. Du et al discovered that the ultimate strength and residual strength of coal samples exhibited a linear increase with confining pressure, and that confining pressure could impede crack expansion while enhancing the energy storage capacity of coal [12].…”
Section: Introductionmentioning
confidence: 99%